Branding in High Fashion Industry in China - Shen, Ye (2007)
Due to the booming economy of the country, the rising disposable income and strong desire of status expression, China is viewed as a promising land for the luxury industry, providing fertile ground for the growth of luxury goods suppliers. More and more famous foreign fashion businesses pour into China and brand them to attract Chinese customers for their higher priced. This paper examines the mindset of the Chinese luxury fashion goods consumers, the drives and their attitude towards luxury fashion brands. In-depth consumer interview were all conducted and the managerial implications for marketers doing branding in China are discussed.